People’s Quality of Life in Relation to Community Attachment in Bangkok Area - Narintorn, Anchalee; Pengjinda, Kanok (Journal of Rattana Bundit University, 2022)
This research aimed to study the level of quality of people’s lives and the level of commitment toward the society in Bangkok, to compare the people’s commitment toward the society categorized according to personal factors in Bangkok, and to study the relationship between the quality of people’s lives related to the commitment toward the society in Bangkok. This study was quantitative research. The samples were 400 people living in the society in Bangkok, specifying samples with the Yamane formula at the 95 percent confidence level, and there was a 5 percent sampling error. The research applied Multi-stage Sampling: cluster random and simple random samplings were used. The instrument was the questionnaires that had been checked for content validity from the experts with an IOC value of 1, and the reliability of the whole questionnaire was .8531. The statistics for data analysis were mean, standard deviation, t-test, One-way ANOVA, multiple comparisons, and Pearson Correlation analysis. The findings revealed that the quality of people’s lives living in Bangkok’s society was at a high level. When considering each side, the physical health and the social relationship were found at a high level. The mental and the environment were at a moderate level. Overall, the level of opinion about the commitment toward the society was high. However, when considering each side, the identity, venue, love in the society, and operation were found at a high level, and social relationship was moderate. There were statistically significant variations in the degree of commitment to the society among Bangkok residents with regard to gender, age, the size of the family, education levels, and average monthly income at a significant level of.05. There were no disparities in the amount of commitment to the society among the people in the society, regardless of their rank, employment, or place of residence. The relationship between the quality of people’s lives and commitment toward the society in Bangkok was a medium level (relation rate (r) = 0.61)